1999
DOI: 10.1038/sj.bjp.0702690
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of adenine nucleotide analogues on shape change and aggregation induced by adenosine 5′‐diphosphate (ADP) in human platelets

Abstract: 1 Adenosine 5'-diphosphate (ADP) induces human blood platelets to aggregate and change shape, and it has been suggested that these two responses are mediated by more than one subtype of ADP receptor. 2 The structure-activity relationships for several analogues of adenine nucleotides in causing aggregation and shape change were measured and compared in washed platelets using an aggregometer. ADP and its analogues 2-methylthioadenosine 5'-diphosphate (2-methylthio-ADP), adenosine 5'(a,b-methylene)diphosphonate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 31 publications
2
29
0
Order By: Relevance
“…This could explain why in diabetic patients strongest correlations were revealed between ATP, but not ADP, platelet levels and different platelet activities (Tables 4 and 5). That suramin, a nonspecific purinergic receptor antagonist (15,16), inhibited thrombinevoked platelet activation and aggregation indicates that ATP/ADP released from activated platelets exert their effects through purinergic receptors (Fig. 2) (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could explain why in diabetic patients strongest correlations were revealed between ATP, but not ADP, platelet levels and different platelet activities (Tables 4 and 5). That suramin, a nonspecific purinergic receptor antagonist (15,16), inhibited thrombinevoked platelet activation and aggregation indicates that ATP/ADP released from activated platelets exert their effects through purinergic receptors (Fig. 2) (29).…”
Section: Discussionmentioning
confidence: 99%
“…Reagents and materials. Reagents for ATP/ADP, acetyl-CoA assays, and suramin, a nonselective purinergic receptors antagonist (15,16), were supplied by Sigma Chemicals (Poznań , Poland); thrombin was from Bio-Med (Lublin, Poland); Commassie Brillant Blue G-250 was from Bio-Rad (Munchen, Germany); and glycine-proline-arginine-proline-NH 2 (GPRP) tetrapeptide was from Bachem (Bubendorf, Switzerland). All other chemicals were of analytical grade.…”
mentioning
confidence: 99%
“…The main objective of our work was to re-examine the effects of adenine triphosphate nucleotides at this receptor, since in several recent studies ATP and its triphosphate analogues were found to be full agonists at native or heterologously expressed P2Y 12 [11,[17][18][19], which does not fit the data previously obtained in blood platelets. Thus, ATP and its adenine triphosphate analogues 2MeSATP and 2ClATP have been shown to be antagonists of ADP-induced adenylyl cyclase inhibition in platelets, a response mediated solely by activation of the P2Y 12 receptor [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…210,211 According to this proposal, the P2T AC receptor would coincide with the platelet P2Y ADP (written in italics to signify that it is not yet cloned) receptor of the nomenclature established by IUPHAR. 2,27 Development of selective platelet P2 receptor antagonists has progressed further than in other cell types, and some have already reached clinical applications.…”
Section: P2 Receptors In Plateletsmentioning
confidence: 99%